Viewers’ Language Styles on Gold Digger: A Multimodal Analysis - Neny Namirah; Didin Nuruddin Hidayat (Universitas Pendidikan Mandalika, 2021)
This paper undertakes viewers' languages style on gold digger using a multimodal analysis. This paper aims to depict the language style of viewer comments on Gold Digger prank in YouTube channel content. Comments on the contents of YouTube channel may differ from active viewers, and the language style they utilized shows the culture, the background, or class where they are from. Therefore center on language style constitutes the main point of this study. The corpus was achieved by viewers' comments on the gold digger prank as one of the YouTube channel contents. The study employed a descriptive qualitative research approach and the content or viewers comments on YouTube as the form of data. The study will focus on the viewers' style language in commenting on the prank content called Gold Digger in the YouTube channel and the style language that the viewers mostly utilized multimodal analysis. Casual style is the dominant style conveyed by the viewers. The viewers' language style varies on the bases of the intimacy, the social interaction and the community from which they come, and the media in which they share their thoughts.